Usefulness of The CHADS2 and CHA2DS2-VASc Scores in Predicting In-Hospital Mortality in Acute Coronary Syndrome Patients: A Single-Center Retrospective Cohort Study - Pramudyo, Miftah; Putra, Iwan Cahyo Santosa; Pratama, Fahmi Bagus; Pranata, Raymond (The Indonesian Heart Association, 2025)
In “Usefulness of The CHADS2 and CHA2DS2-VASc Scores in Predicting In-Hospital Mortality in Acute Coronary Syndrome Patients: A Single-Center Retrospective Cohort Study” (Indonesian Journal of Cardiology, 44(1), 17-27. https://doi.org/10.30701/ijc.1294), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1294. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error. DOI of original article: https://doi.org/10.30701/ijc.1294